2021
DOI: 10.1029/2021ja029156
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of Foreshock Transients in the Midtail Foreshock

Abstract: Midtail foreshock transients develop under mostly similar formation conditions as dayside ones • Almost all midtail foreshock transients have electron heating which is proportional to the solar wind speed • Foreshock transients may be stable for tens of minutes and continuously disturb the local bow shock and accelerate particles Supporting Information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 61 publications
5
29
0
Order By: Relevance
“…As for the Mach numbers, Figure 3e of the Alfvén Mach numbers shows an increasing preference for higher Alfvén Mach numbers for all event types and peaks between 11 and 13 Alfvén Mach numbers, after which the occurrence rates decrease, consistent with Facskó et al (2009) and Liu, Zhang, Wang, et al (2021). The same trend holds qualitatively after calculating the local the Alfvén Mach number at the local bow shock surface, shown in Figure 3f.…”
Section: Solar Wind Conditions Of Eventssupporting
confidence: 57%
“…As for the Mach numbers, Figure 3e of the Alfvén Mach numbers shows an increasing preference for higher Alfvén Mach numbers for all event types and peaks between 11 and 13 Alfvén Mach numbers, after which the occurrence rates decrease, consistent with Facskó et al (2009) and Liu, Zhang, Wang, et al (2021). The same trend holds qualitatively after calculating the local the Alfvén Mach number at the local bow shock surface, shown in Figure 3f.…”
Section: Solar Wind Conditions Of Eventssupporting
confidence: 57%
“…This could explain why in Liu, Turner, et al. (2016), a thick TD forms an HFA, and a thin TD forms an FB during the same time interval, and why a larger magnetic shear angle favors the formation of HFAs (e.g., Liu et al., 2021; Schwartz et al., 2000; Zhao et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“… 2017b ) and ARTEMIS (Liu et al. 2021 ) observations also found that the solar wind density does not affect the HFA, SHFA, and FB occurrence, but that low IMF strengths favor occurrence. High fast magnetosonic Mach number ( ) also favors the formation of HFAs.…”
Section: Transient Processes In the Foreshock Bow Shock And Magnetosh...mentioning
confidence: 93%
“…The statistical study of foreshock transients in the midtail foreshock also showed that high solar wind Alfvén Mach number is a favorable condition (Liu et al. 2021 ). PIC simulations by An et al.…”
Section: Transient Processes In the Foreshock Bow Shock And Magnetosh...mentioning
confidence: 98%